Comparison of non-invasive ventilation use and outcomes in children with Down syndrome and other children using this technology - Valji, Rafiaa; Castro-Codesal, Maria L.; Lewis, Melanie; MacLean, Joanna E. (Frontiers in Sleep, 2023)
Rationale: Children with Down syndrome (DS) make up a substantial portion of long-term non-invasive ventilation (LT-NIV) users though it is unclear if their unique features alter LT-NIV efficacy or use. The aim of this study is to compare the use and outcomes of LT-NIV for children with DS and a matched comparison (MCG). Methods: This is a sub-study of a 10-year retrospective review of children initiated on LT-NIV in Alberta, Canada (N=622). Children with DS (n=106) were matched in a 1:2 ratio with other children using LT-NIV based on age and therapy start date. Data was collected from medical and sleep laboratory records. Results: Upper airway disease was the most common indication for LT-NIV in both groups, though was higher in children with DS (DS: 90% vs MCG: 50%, OR 8.64 [95% CI 4.38-17.04]). Sleep and respiratory parameters, at the baseline diagnostic sleep study and the change from baseline to treatment study, did not differ between groups. Nasal masks were the predominant mask type in both children with DS (55%) and the MCG (66%) with more children with DS, compared to the MCG, using full face masks (DS: 45 vs MCG: 33%, p< 0.05). Continuous positive airway pressure was used more often in children with DS (93.3% vs 69.2%, p<0.001) while bilevel-positive airway pressure was more common in the MCG (DS: 6.7% vs MCG 30.8%, p<0.001). Children with DS were followed longer than children in the MCG (DS: 2.4 [IQR 2.8] vs MCG: 1.8 [IQR 2.7] years, p<0.05). Adherence was lower in children with DS at both 6-12 month follow-up and most recent visit with a similar decrease in adherence in both groups over the follow-up period (0.0 [IQR 1.4] vs -0.3 [IQR 2.0]. Despite this, 66% and 49% of children with DS used LT-NIV for more than 4h/night at 6-12 month and most current visit respectively. Discontinuation of LT-NIV and mortality did not differ between groups. Conclusion: LT-NIV is a common and efficacious treatment in children with DS used predominantly for upper airway obstruction. While adherence is lower, the majority of children with DS are successful at using LT-NIV.